2022
DOI: 10.1007/s00103-022-03511-4
|View full text |Cite
|
Sign up to set email alerts
|

Anhaltende Fatigue als Folge einer COVID-19-Infektion bei Beschäftigten im Gesundheitswesen: Risikofaktoren und Auswirkungen auf die Lebensqualität

Abstract: Zusammenfassung Hintergrund und Ziel Durch ihre Tätigkeit sind Menschen aus medizinisch-pflegerischen Berufen einem erhöhten Risiko für eine SARS-CoV-2-Infektion ausgesetzt und dadurch öfter von Krankheitsfolgen betroffen. In bisherigen Studien wurde als häufigste Krankheitsfolge die postvirale Fatigue (Erschöpfungssyndrom nach viraler Infektion) identifiziert. Das Ziel der Studie war die Untersuchung von Risikofaktoren für anhaltende Fatiguesymptome infolge einer COVID-19-Infektion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
2
6
0
2
Order By: Relevance
“…For example, a meta-analysis showed that after COVID-19, fatigue can significantly worsen the quality of life but is also associated with other symptoms such as dyspnoea, anosmia, sleep disturbances and impaired mental health [ 34 ]. For our study population, the assessments by Haller et al [ 35 ] were also able to show that fatigue after SARS-CoV-2 infection is associated with a reduced quality of life, increased psychological distress, lower subjective health status and more frequent ability to work. Overall, our results indicate that health-related quality of life is considerably reduced for both physical and mental health in those with PCS.…”
Section: Discussionmentioning
confidence: 60%
“…For example, a meta-analysis showed that after COVID-19, fatigue can significantly worsen the quality of life but is also associated with other symptoms such as dyspnoea, anosmia, sleep disturbances and impaired mental health [ 34 ]. For our study population, the assessments by Haller et al [ 35 ] were also able to show that fatigue after SARS-CoV-2 infection is associated with a reduced quality of life, increased psychological distress, lower subjective health status and more frequent ability to work. Overall, our results indicate that health-related quality of life is considerably reduced for both physical and mental health in those with PCS.…”
Section: Discussionmentioning
confidence: 60%
“…This could be indicative of a development of psychological items due to an ongoing inflammation in the brain or the persistent low physical capability, which can negatively affect mental health [ 29 ]. A recent review by Haller et al [ 30 ] showed that persistent fatigue is a risk factor for a decreased life quality and work capacity. Furthermore, they observed that pre-existing psychological disorders also increase the risk for the Post-COVID syndrome [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Haller et al [ 30 ] showed that persistent fatigue is a risk factor for a decreased life quality and work capacity. Furthermore, they observed that pre-existing psychological disorders also increase the risk for the Post-COVID syndrome [ 30 ]. Therefore, our results that psychological disorders increased over time, could indicate that the life quality decreases with persistent fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Wie unsere Daten zeigen, gefährden Beeinträchtigung durch eine kognitive Fatigue die Rückkehr ins Erwerbsleben. Ähnliche Befunde liefert eine Befragung unter Beschäftigten im Gesundheitswesen, in der ein Zusammenhang zwischen einer schweren Fatigue in Folge einer Covid-19-Infektion und häufigerer Arbeitsunfähigkeit beobachtet wurde 10 . Neurologisch-kognitive Corona-Symptome waren in unserer Stichprobe kein signifikanter Risikofaktor für die Rückkehr ins Erwerbsleben.…”
Section: Diskussionunclassified
“…Von den Befragten bestand bei 40% eine Arbeitsunfähigkeit aufgrund persistierender Symptome der Covid-19-Erkrankung 9 . Eine groß angelegte Befragung der Berufsgenossenschaft für Gesundheitsdienst und Wohlfahrtspflege unter 2035 Versicherten ergab, dass 10% der Covid-19-Infizierten noch nach Monaten eine schwere Fatigue aufwiesen und diese mit großen psychischen Belastungen, einer beeinträchtigten Lebensqualität und einer häufigeren Arbeitsunfähigkeit einherging 10 . Ein systematisches Review von Gualano et al stellte unter hospitalisierten Covid-19-Patient*innen eine verzögerte Rückkehr an den Arbeitsplatz und berufsbezogene Einschränkungen fest 11 .…”
Section: Introductionunclassified